Health Facilities Distribution Mapping in Addis Ababa, Ethiopia (Global Journal of Human-Social Science, 2016)
Geographical Information Systems (GIS) have been used widely in many countries to map health-related events and the results are used for planning of health services and in assessing clusters of health facilities. This project demonstrates the application of GIS in the mapping of health facilities in Addis Ababa particularly Gulele sub-city; the ArcGIS 9.3 software was used to map and evaluate the spatial clustering of health facilities in the study area. The study was conducted using primary and secondary data collected from various areas with GPS technology. The results suggest that new health facilities should be built in the woredas of Gulele sub-city. The method of analysis employed point pattern analysis used to evaluate the physical distribution of point events and test whether there is a significant clustering of points in a particular area and also ratio. The project has been developed for all participating service agencies to give an overview 'map' of the health service sector. The project is designed to assist the participating health services in developing a good understanding of the community in the recovery context, enabling strategic planning and coordination of services to the increased need of the population of the subcity in the area of health facilities.
Keywords: GIS; health facility; mapping